Firm-specific pay premiums and the gender wage gap in 21 European countries - Jan-Luca Hennig; Balazs Stadler (ZBW - Leibniz Information Centre for Economics, 2021)
We study how firm premia influence the gender wage gap for 21 European countries over 12 years. We use a quadrennial harmonized matched employer-employee data set to estimate gender-specific firm premia. Subsequently, we decompose the firm-specific wage premia differential into a within- and between-firm component. We show that, on average in Europe, the former mainly accounts for the decline in the pay gap between 2002 and 2014, while the latter does not change significantly. An analysis of the subgroups by age and gender reveals heterogeneity in the development of the components. We pay particular attention to the development of each component across the life cycle and find that the between-firm component is associated with an increase in the gender pay gap across the life cycle. The decomposition of firm premia then allows us to investigate how institutional settings relate to each component. For the within-firm component we exploit firm-level differences in the collective bargaining regime, and we link family policies to the betweenfirm component. Centralized wage bargaining is associated with higher gender wage gaps, whereas family policies enabling and encouraging women to return to the labor market after family formation reduces the between-firm component.
Keywords: J16; J18; J31; J52; 330; Gender Wage Gap; Firm Premia; Decomposition; Institutional Settings